Elimination of Eight Viruses and Two Viroids from Preclonal Candidates of Six Grapevine Varieties (Vitis vinifera L.) through In Vivo Thermotherapy and In Vitro Meristem Tip Micrografting - Vanja Miljanić; Denis Rusjan; Andreja Škvarč; Philippe Chatelet; Nataša Štajner (Plants, 2022)
Viruses and virus-like organisms are a major problem in viticulture worldwide. They cannot be controlled by standard plant protection measures, and once infected, plants remain infected throughout their life; therefore, the propagation of healthy vegetative material is crucial. In vivo thermotherapy at 36–38 °C for at least six weeks, followed by meristem tip micrografting (0.1–0.2 mm) onto in vitro-growing seedling rootstocks of Vialla (Vitis labrusca × Vitis riparia), was successfully used to eliminate eight viruses (grapevine rupestris stem pitting-associated virus (GRSPaV), grapevine Pinot gris virus (GPGV), grapevine fanleaf virus (GFLV), grapevine leafroll-associated virus 3 (GLRaV-3), grapevine fleck virus (GFkV), grapevine rupestris vein feathering virus (GRVFV), grapevine Syrah virus-1 (GSyV-1), and raspberry bushy dwarf virus (RBDV)), as well as two viroids (hop stunt viroid (HSVd) and grapevine yellow speckle viroid 1 (GYSVd-1)) from preclonal candidates of six grapevine varieties (Vitis vinifera L.). A half-strength MS medium including vitamins supplemented with 30 g/L of sucrose and solidified with 8 g/L of agar, without plant growth regulators, was used for the growth and root development of micrografts and the subsequently micropropagated plants; no callus formation, hyperhydricity, or necrosis of shoot tips was observed. Although the overall regeneration was low (higher in white than in red varieties), a 100% elimination was achieved for all eight viruses, whereas the elimination level for viroids was lower, reaching only 39.2% of HSVd-free and 42.6% GYSVd-1-free vines. To the best of our knowledge, this is the first report of GPGV, GRVFV, GSyV-1, HSVd, and GYSVd-1 elimination through combining in vivo thermotherapy and in vitro meristem tip micrografting, and the first report of RBDV elimination from grapevines. The virus-free vines were successfully acclimatized in rockwool plugs and then transferred to soil.